3D optical measurement techniques. (1st March 2023) - Engel, Thomas
Abstract: The field of optical 3D metrology is gaining significant interest in the past years. Optical sensors can probe the geometry of workpieces and biological samples very fast, highly accurate and without any tactile physical contact to the object's surface. In this respect, optical sensors are a pre-requisite for many applications in the big trends like Industrial Internet of Things, Industry 4.0 or Medicine 4.0. The interest for optical 3D metrology is shifting from a metrology for quality assurance in industrial production to "digitize the real world" to facilitate a precise digital representation of an object or an environment for documentation or as input data for virtual applications like digital fab or augmented reality. The aspiration to digitize the world necessitates fast and efficient contact free sensing principles of appropriate accuracy for solid and even soft objects with a variety of colour, surface texture and lighting conditions. This review article tries to give a concise conceptual overview about the evolution of a broad variety of optical measurement principles that evolved and gained some importance in the field of 3D metrology for industrial 3D applications and their related technological enablers.